2007
DOI: 10.1016/j.rvsc.2006.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Oral efficacy of Vero cell attenuated porcine epidemic diarrhea virus DR13 strain

Abstract: A Vero cell attenuated porcine epidemic diarrhea virus (PEDV) strain, DR13, was distinguished from wild-type PEDV using restriction enzyme fragment length polymorphism (RFLP). Cell attenuated DR13 was orally or intramuscularly (IM) administered to late-term pregnant sows, and mortality resulting from the highly virulent PEDV challenge was investigated in passively immunized suckling piglets of the two different groups. The mortality rate of the oral group (13%) was lower than that of the IM group (60%). In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 18 publications
2
113
0
1
Order By: Relevance
“…Further, this vaccine candidate remained safe even after three back passages in piglets [88]. Piglet mortality can be reduced by orally inoculating pregnant sows with the DR13 strain.…”
Section: Vaccinesmentioning
confidence: 98%
See 2 more Smart Citations
“…Further, this vaccine candidate remained safe even after three back passages in piglets [88]. Piglet mortality can be reduced by orally inoculating pregnant sows with the DR13 strain.…”
Section: Vaccinesmentioning
confidence: 98%
“…The past few years have seen several useful modifications of the basic RT-PCR method. For instance, it is possible to estimate the potential transmission of PEDV by comparing viral shedding load with a standard internal control DNA curve [72], as well as to perform multiplex RT-PCR to detect PEDV in the presence of various viruses [73]-a technique that is particularly useful for rapid, sensitive, and cost-effective diagnosis of acute swine viral gastroenteritis). The commercial dual priming oligonucleotide (DPO) system (Seegene, Seoul, Korea) was also developed for the rapid differential detection of PEDV.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…On the farm where the data for the present study was collected, the immunization technique used involved feeding the sows the feces and minced intestines of infected piglets. The piglets delivered from seropositive sows might acquire passive immunity from their mothers (Olanratmanee et al, 2010), reducing their mortality as a result of immune resistance to the PED virus (Song et al, 2007). In addition, previous studies reported that passive lactogenic immunity to PED virus is important for suckling piglet protection due to an immature immune system of the neonatal suckling piglet (Langel et al, 2016), and antibody provided in colostrum and milk protects the piglet in the interval between birth and development of a functional immune system (Poonsuk et al, 2016).…”
Section: Post-weaning Performancementioning
confidence: 99%
“…26 Protection against the enteric disease is primarily dependent on the presence of secretory IgA antibodies in the intestinal mucosa, and oral vaccination can stimulate mucosal immunity and produce protective mucosal and serum IgA antibodies more effectively than other vaccination routes such as intramuscular (IM). 26 Song et al 118 reported that oral administration with live-attenuated PEDV DR13 vaccine in pregnant sows reduced the mortality of suckling piglets more effectively compared to those administered by IM route (13% versus 60%), and exhibited higher IgA antibody levels. However, some challenges exist in the development of an oral PEDV vaccine, which include balancing sufficient virus attenuation and vaccine immunogenicity, improving the inconvenience of inoculation in swine herds, and developing effective adjuvants.…”
Section: Issues On Current Development Of Pedv Vaccinesmentioning
confidence: 99%